2014
DOI: 10.1017/s1041610214001185
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to change of composite and frequency scores of the neuropsychiatric inventory in mild cognitive impairment

Abstract: Our findings support the hypothesis that in MCI, as in dementia, the NPI frequency score is not more sensitive to treatment-related change than the composite score. As the severity score adds information, the use of the composite score has better performance characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Cognitive function was evaluated using several measures . Episodic memory was evaluated with the composite score of immediate recall and delayed recall.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive function was evaluated using several measures . Episodic memory was evaluated with the composite score of immediate recall and delayed recall.…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive function was evaluated using several measures. [34][35][36] Episodic memory was evaluated with the composite score of immediate recall and delayed recall. For the immediate word recall, the participants were asked to repeat 10 unrelated words and had to immediately recall as many words as they could.…”
Section: Outcome: Cognitive Functionmentioning
confidence: 99%
“…The 15-item Geriatric Depression Scale [GDS-15, 27] is a screening tool with higher overall total scores (range 0–15) indicating higher depression levels, and studies have reported evidence of concurrent validity [2830] and diagnostic accuracy [30, 31]. The Neuropsychiatric Inventory [NPI, 32] is an assessment tool for frequency and severity of behavioural and psychological symptoms in dementia with higher overall scores (range 0–144) indicating poorer health, and studies have reported evidence of sensitivity to treatment-related changes [33, 34]. The Bristol Activities of Daily Living Scale [BADL, 35] is an assessment tool for functional decline among people with dementia in terms of their ability to carry out daily living activities independently with higher overall total scores (range 0–60) indicating more dependence, and studies have reported convergent validity and sensitivity to treatment-related changes [36, 37].…”
Section: Methodsmentioning
confidence: 99%
“…M ood a n d b e h av i o r a l r i s k fac to r s The Spanish validated version of the Cornell Scale for Depression in Dementia (CSDD) (Pujol et al, 2001;Towsley et al, 2012) was used to assess signs and symptoms of major depression. The validated Spanish version of the Neuropsychiatric Inventory (NPI) (Boada et al, 2005;Cummings et al, 2014) was employed to evaluate the frequency and severity of neuropsychiatric disturbances.…”
Section: Fallsmentioning
confidence: 99%